THE EFFECT OF WORK LIFE BALANCE AND COMPENSATION ON ORGANIZATIONAL COMMITMENT OF EMPLOYEES OF PT BANK NEGARA INDONESIA (PERSERO) MAIN BRANCH OFFICE, MAKASSAR CITY - Alam, Nurul Itha Prihasti; Dipoatmodjo, Tenri Sayu Puspitaningsih; Hamka, Rezky Amalia (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the influence of Work Life Balance and Compensation on Organizational Commitment among employees of PT Bank Negara Indonesia (Persero) Tbk Main Branch Office in Makassar City. The background of this study is based on the phenomenon of imbalance between work demands and employees' personal lives and the perception of some employees that the compensation received is not commensurate with the workload they undertake. This study uses a quantitative method with an explanatory approach, where data is obtained through distributing questionnaires to 105 respondents determined using the Slovin formula from a total population of 146 employees. Data analysis was carried out using multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that Work Life Balance has a positive and significant effect on Organizational Commitment, meaning that the better the balance between work and personal life of employees, the higher their commitment to the organization. Compensation also has a positive and significant effect on Organizational Commitment, indicating that fair and adequate compensation can increase employee loyalty and sense of belonging to the company. Simultaneously, Work Life Balance and Compensation have a positive and significant effect on Organizational Commitment. Thus, this study emphasizes the importance of implementing work-life balance policies and fair compensation systems to strengthen employee commitment to the organization.Keywords: Work Life Balance,Compensation, Organizational Commitment, Employees